Improvement and stabilization of rice production by delaying sowing date in irrigated rice system in central China. (21st November 2019) - Tu, Debao; Jiang, Yang; Liu, Min; Zhang, Lijuan; Chen, Linlin; Cai, Mingli; Ling, Xiaoxia; Zhan, Ming; Li, Chengfang; Wang, Jinping; Cao, Cougui
Abstract: BACKGROUND: Climate change has posed great challenges to rice production. Temperature and solar radiation show significant variations in central China. This study aims to analyze the responses of different rice genotypes to the variations of temperature and solar radiation in central China, and to find the way of identifying the optimal sowing date to improve and stabilize rice production. For this end, four rice genotypes (two Indica and two Japonica cultivars) were cultivated at two locations under irrigation conditions in 2 years with six sowing dates. RESULTS: We investigated variations of rice grain yield, resource use efficiency, average daily temperature and solar radiation during different phenological stages. Rice grain yield could increase by about 2–17% in central China. Compared with solar radiation, temperature was a more important factor affecting rice grain yield in central China. The grain yield showed great correlation with the means temperature during different phenological stages, especially during the first 20 days after heading (GT20). Besides our results demonstrated that the grain yield displayed slender variations when the GT20 was within 24.9–26.4 °C. However, GT20 was higher than 26.4 °C in most cases, which became more frequent due to climate changes. Analysis of climate change during the last 25 years revealed that the frequency of GT20 within 24.9–26.4 °C was increased by the delay of sowing date. CONCLUSION: We propose that delaying sowing date to achieve the optimal GT20 (24.9 °C–26.4 °C) can be an effective strategy to stabilize and improve rice grain yield and resource use efficiency in central China. © 2019 Society of Chemical Industry